Kinerja Karyawan Ditinjau Dari Disiplin Dan Motivasi Kerja - Ahmad K (Economics and Digital Business Review, 2024)
The aim of this study was to identify and analyze the simultaneous and partial effects of labor discipline and work motivation on employee job performance at PT. Bumi Surya Selaras Kecamatan Luyo Kabupaten Polewali Mandar. This research approach is a quantitative approach, the purpose of this study is a descriptive study, this type of research is a survey. The site where this study was conducted at PT. Bumi Surya Selaras. The population in this study was all full-time employees at PT. Bumi Surya Selaras totaling 50 people. The saturation sample was used to determine the sample for this study in order to obtain a representative sample of the population. Data analysis was performed using multiple linear regression. This is shown through the results of analysis, work discipline and work motivation have a significant influence on employee performance at PT. Bumi Surya Selaras.